Body integrity identity disorder: clinical features and ethical dimensions. (29th October 2018) - Barrow, Emma; Oyebode, Femi
SUMMARY: Body integrity identity disorder (BIID) is a rare and complex identity disorder described by the desire to acquire a physical disability and an associated sense of incompleteness at being able-bodied. Individuals with the disorder often delay presentation until later in life because of perceived stigma about wishing to acquire a physical disability, and may have sought amputation already through 'underground' means or self-harm (attempts at self-amputation). In this article we present an account of the recent history and origins of the disorder, from its early descriptions and case reports through to the current neuropsychiatric theory of right superior parietal lobe dysfunction as basis for the disorder. We consider the epidemiology, pathogenesis and clinical features of this identity disorder of bodily integrity, highlighting the associations with conditions such as gender identity disorder. With this we then discuss the ethical considerations for available treatment options, mainly elective surgical amputation. LEARNING OBJECTIVES: Understand the current definition and clinical features of body integrity identity disorder Be familiar with the conceptual history of the disorder, epidemiology and current neuropsychiatric perspective Be aware of the ethical aspects of elective surgical amputation as a treatment for the disorder DECLARATION OF INTEREST: None.